Gender and the radical right in Western Europe: a comparative analysis of policy agendas - Akkerman, Tjitske (Patterns of prejudice, 2015)
Systematic research comparing the views of populist radical-right parties with respect to gender issues is still scarce. Akkerman's article aims to fill this gap by comparing the positions of the six most successful populist radical-right parties in Western Europe. Her focus is on gender issues in the policy domain of family relations, on the one hand, and in that of immigration and integration, on the other. A combination of quantitative and qualitative analyses of external and internal party documents has been used to assess the positions of the main populist radical-right parties with regard to these two policy domains. Akkerman's analysis shows that, in the domain of family relations, the parties are traditionally conservative or adopt a more flexible modern conservative position. Compared to mainstream right-wing parties, which are consistently more liberal than their radical-right counterparts, conservatism on issues relating to the family sets the radical parties clearly apart. Yet, as this particular profile tends to become less salient over time, it is doubtful that gender issues in this traditional policy domain will continue to be a defining characteristic of these parties. Gender issues have gained importance for populist radical-right parties in the domain of immigration and integration policies but, in this context, the parties do not display a conservative profile. They tend to emphasize the principles of gender equality and sometimes also gay rights, although these commitments are mainly rhetorical and instrumental to anti-immigration and anti-Islam agendas. Conservative views of gender remain the defining, albeit less salient, characteristic of these parties.